1988
DOI: 10.1530/acta.0.1170295
|View full text |Cite
|
Sign up to set email alerts
|

GHRH-induced GH response in patients with senile dementia of the Alzheimer type

Abstract: Abstract. To clarify the functional state of the somatotropinergic system at the hypothalamo-hypophyseal level in senile dementia of the Alzheimer type, the GHRH test was performed in three groups of subjects: a) healthy elderly subjects; b) early onset senile dementia patients; and c) late onset senile dementia patients. Intravenous administration of GHRH(1–44)NH2 (100 μg) elicited a marked plasma GH response with a maximum peak (709.54 ± 259.0 pmol/l; P < 0.005) 60 min after injection in patients with ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
6
9
0
Order By: Relevance
“…However, the demented subjects exhibited a delay in the time of peak occurrence. A similarly delayed response has been reported by Nemeroff et al [4] in AD and by Cacabelos et al [17] in SDAT.…”
Section: Discussionsupporting
confidence: 82%
“…However, the demented subjects exhibited a delay in the time of peak occurrence. A similarly delayed response has been reported by Nemeroff et al [4] in AD and by Cacabelos et al [17] in SDAT.…”
Section: Discussionsupporting
confidence: 82%
“…Unchanged GH basal levels and preserved responses to various stimuli -such as GHRH and pyridostigminehave been reported in unselected groups of patients with Rollero/Murialdo/Fonzi/Garrone/Gianelli/ Gazzerro/Barreca/Polleri dementia [35][36][37][38][39]. In patients with severe dementia, we did find increased GH baseline levels and lower GH responses to GHRH administered alone or after pyridostigmine pretreatment [15].…”
Section: Discussionsupporting
confidence: 61%
“…As in the present study, some authors found no difference in GH response to GHRH with regard to the onset of dementia [16], while Cacabelos et al [41] re ported a more marked GH response to GHRH in patients with early-onset AD. Four out of 15 patients studied by us had early-onset disease and a clear GH response to all stimuli, but this pattern was also observed in older patients with late-onset disease.…”
Section: Discussionsupporting
confidence: 58%